PHYSICAL AND MECHANICAL PROPERTIES OF THE WOOD FROM Parkia gigantocarpa DUCKE - Eliazel Vieira Rondon; Dirceu Lúcio Carneiro de Miranda; Mariele Cunha de Miranda; Patrícia Aparecida Rigatto Castelo (Ciência da Madeira, 2012)
The objective of this study was to determine some physical and mechanical properties of the wood from Parkia gigantocarpa Ducke and assess its technological potential in order to establish the uses of that species. Three 14-year-old trees from an experimental planting were used, from which short logs in lengths equivalent to the base of the three, 25, 50, 75 and 100% of the commercial height were produced. In each of such heights a disc was collected to establish the basic specific mass. The anisotropic shrinkage, according to COPANT 462 (1972), and some mechanical properties, according to ASTM D 143 (1995), were also determined. In order to do that, the first two-meter-long log of each tree was used. The data were analyzed using descriptive statistics as well as the comparison of the resultsobtained with similar studies found in related literature. The wood from Parkia gigantocarpa is light, with an average density of 0,48 g.cm-³, enabling its use in lamination. According tothe mechanical results, this species is considered unsuitable for structural purposes and due to high shrinkage of the wood it is also not recommended for solid wood furniture manufacturing, doors, windows and musical instruments.